2008
DOI: 10.1007/s12355-008-0028-7
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly management of red rot disease of sugarcane with Trichoderma strains

Abstract: Eighty strains of Trichoderma harzianum and T. viride occurring in sugarcane rhizosphere soil of sub-tropical zone were isolated on Trichoderma specific medium and tried screened in vitro against Colletotrichum falcatum. Highly potent ones (Th 37 & Th 38) were tried to manage red rot disease under field conditions. Healthy setts were treated by applying Trichoderma mixed culture (TMC) of T. harzianum strains grown in sterilized maize bran (2 kg) and subsequently mixed with sterilized press mud or FYM (20 kg) /… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…Similarly, increased P uptake improved the growth and yield of infected citrus ( Citrus limon ) trees (Zhao et al ., ). Our results indicate that T. virens is required to mobilize and increase nutrient uptake by the plant; T. virens is more efficient and competitive than many other soil microbes in promoting growth and improving plant fitness (Hermosa et al ., ; Singh et al ., ). Therefore, we can hypothesize that the energy required to induce TriV_JSB100‐mediated FOL resistance does not affect tomato plant development.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, increased P uptake improved the growth and yield of infected citrus ( Citrus limon ) trees (Zhao et al ., ). Our results indicate that T. virens is required to mobilize and increase nutrient uptake by the plant; T. virens is more efficient and competitive than many other soil microbes in promoting growth and improving plant fitness (Hermosa et al ., ; Singh et al ., ). Therefore, we can hypothesize that the energy required to induce TriV_JSB100‐mediated FOL resistance does not affect tomato plant development.…”
Section: Discussionmentioning
confidence: 97%
“…The data presented are from representative experiments that were repeated at least four times with similar results. microbes in promoting growth and improving plant fitness (Hermosa et al, 2012;Singh et al, 2008). Therefore, we can hypothesize that the energy required to induce TriV_JSB100-mediated FOL resistance does not affect tomato plant development.…”
Section: Discussionmentioning
confidence: 99%
“…Eco‐friendly management of red rot of sugarcane has been performed with Trichoderma strains . Later, it was reported that by Hassan et al that plant growth‐promoting rhizobacteria has potential to be used as biopesticide to control red rot disease of sugarcane.…”
Section: Introductionmentioning
confidence: 99%
“…Srivastava et al (2006a, b) observed enhancement in germination and yield parameters of sugarcane in both plant and ratoon crops by the use of Trichoderma sp. Singh et al (2008) and Yadav et al (2008) have also reported that red rot disease of sugarcane can be managed by the application of T. harzianum since it acts directly on C. falcatum and induces systemic resistance in plants developed from treated setts. Reduction in disease incidence and enhancement in growth parameters in various crops by the use of Trichoderma spp.…”
Section: Ratoon Crop : Yieldmentioning
confidence: 99%